(untitled) (Construction Economics and Building, 2014)
Cost is an important measure of project success and clients will expect a reliable forecast at the early stage of construction projects to inform their business decision. This study was undertaken to investigate the current practices in managing cost of mechanical and electrical (M&E) services in buildings. The perceptions of practitioners on the benefits of adopting Standard – Based Pricing Mechanism for M&E services as used for building fabrics and finishes was ascertained. The methodology adopted for the study was semi – structure interview and questionnaire survey. Inferential statistics technique was used to analyse the data collected. The results revealed that, M&E services tender documents are often based on lump sum contract. Practitioners are of the opinion that the adoption of Standard – Based Pricing Mechanism (SBPM) could enhance the quality of M&E services price forecast; ensure active post contract cost monitoring and control; encourage collaborative working relationship; enhance efficient whole life cycle cost management; improve risk management and facilitate efficient tendering process. The study suggested the development of local Standard Method of Measurement for M&E services and proposed strategies to facilitate the adoption of SBPM as basis for forecasting contract price of mechanical and electrical services in buildings.